KESIAPAN ETIKA PENGGUNAAN AI GENERATIF PADA TUGAS AKADEMIK: PENGARUH PEMAHAMAN INTEGRITAS AKADEMIK DAN PERSEPSI MANFAAT-RISIKO - Eka Ramadhani Putra; Putri Ramadani; Fitri Safnita (LPPM Unbaja, 2026)
Generative AI tools are increasingly used by students to support academic tasks such as drafting, coding, and summarizing. While these tools may improve efficiency and learning, they also introduce ethical risks related to academic integrity, transparency, privacy, and misinformation. This study examines ethical readiness for using generative AI in academic assignments and tests the effects of students' understanding of academic integrity and their perceived benefit-risk appraisal. A cross-sectional survey was administered to undergraduate students in semester 4 (N = 180). Data were analyzed using multiple regression. Key findings (simulated example): integrity understanding positively predicted ethical readiness (beta = 0.348, p <0.001), perceived risk also showed a positive effect (beta = 0.185, p = 0.013), while perceived benefit was not significant (beta = -0.053, p = 0.498).